Mucociliary dysfunction in HIV and smoked substance abuse - Chinnapaiyan, Srinivasan; Unwalla, Hoshang J. (Frontiers in Microbiology, 2015)
Impaired mucociliary clearance (MCC) is a hallmark of acquired chronic airway diseases like chronic bronchitis associated with chronic obstructive pulmonary disease (COPD) and asthma. This manifests as microbial colonization of the lung consequently leading to recurrent respiratory infections. People living with HIV demonstrate increased incidence of these chronic airway diseases. Bacterial pneumonia continues to be an important comorbidity in people living with HIV even though anti-retroviral therapy has succeeded in restoring CD4+ cell counts. People living with HIV demonstrate increased microbial colonization of the lower airways. The microbial flora is similar to that observed in diseases like cystic fibrosis and COPD suggesting that mucociliary dysfunction could be a contributing factor to the increased incidence of chronic airway diseases in people living with HIV. The three principal components of the MCC apparatus are, a mucus layer, ciliary beating and a periciliary airway surface liquid (ASL) layer that facilitates ciliary beating. Cystic fibrosis transmembrane conductance regulator (CFTR) plays a pivotal role in regulating the periciliary airway surface liquid. HIV proteins can suppress all the components of the MCC apparatus by increasing mucus secretion and suppressing CFTR function. This can decrease ASL height leading to suppressed ciliary beating. The effects of HIV on MCC are exacerbated when combined with other aggravating factors like smoking or inhaled substance abuse, which by themselves can suppress one or more components of the MCC system. This review discusses the pathophysiological mechanisms that lead to MCC suppression in people living with HIV who also smoke tobacco or abuse illicit drugs.